Fundamentals and applications of ultrasonic waves - Cheeke, J. David N. (CRC series in pure and applied physics, 2002)
Suitable for senior undergraduates, beginning graduate students, and those just entering the field of ultrasonics, this book offers a treatment of ultrasonic waves in isotropic media. It focuses on the physics of acoustic waves, their propagation, and the different modes that can be excited in various geometries